Literature in the EFL Classroom in KSA: Rectifying a Relationship at Odds - ALKHODIMI, K.A; AL-AHDAL, A.A.M.H (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTA language is better, if not exclusively, learned in context. Since languages are representative of the culture of their speakers, EFL teaching/learning through the literary creations of a language can be beneficial in many respects. To mention a few, it encourages and fosters tolerance, lateral thinking and purposeful language use, provides varied and wide instances and possibilities of language use, and exposes learners to real-life situations of the target language. Literature is thus an important, if not indispensable, addition to EFL courses and curricula. However, the task of selecting appropriate literary works for inclusion in foreign language syllabi is a challenge that requires sufficient attention and taking carefully considered and well-thought-out measures in its own right. The experience of teaching EFL in Saudi Arabian universities shows that learners are, in general, disinclined, and at times even outright averse, to studying literary content in spite of the fact that they have a few years of exposure to it prior to the university. Literature, nevertheless, is an inseparable component of syllabi in higher education institutes. This paper aimed to find the reasons for this and elaborated on the benefits of literature in enriching and enhancing EFL learners’ experience. It also proposed ideas to make reading literary texts an interesting experience for EFL learners. The focus of the study is the assessment of the attitudes and perceptions of sophomore EFL learners and teachers in College of Languages and Translation, Imam Muhammad Ibn Saud Islamic University (IMBSIU) and College of Sciences and Arts, Methnab, Qassim University (QU), towards studying literature in English. The study tried to reconcile, and bridge, learners’ literary preferences with educational goals in respect to literary components in Saudi EFL classrooms. The findings were manifold but overall showed improved outcomes following the administration of the treatment, especially in terms of motivation, engagement and communicative output. RESUMENUn idioma es mejor aprendido en contexto. Dado que los idiomas son representativos de la cultura de sus hablantes, la enseñanza/aprendizaje del inglés como lengua extranjera (EFL por sus siglas en inglés) a través de las creaciones literarias de un idioma puede ser beneficioso en muchos aspectos. Por mencionar algunos, alienta y fomenta la tolerancia, el pensamiento lateral y el uso intencionado del lenguaje, proporciona instancias y posibilidades variadas y amplias de uso del lenguaje y expone a los alumnos a situaciones de la vida real del idioma de destino. La literatura es una adición importante a los cursos y planes de estudio de EFL. La experiencia de enseñar EFL en las universidades de Arabia Saudita muestra que los estudiantes no están dispuestos a estudiar contenido literario a pesar de que tienen algunos años de exposición antes de la universidad. La literatura es un componente inseparable de los programas de estudio en la educación superior. Este documento tuvo como objetivo encontrar las razones de esto y explicó los beneficios de la literatura para enriquecer y mejorar la experiencia de los estudiantes de EFL. También propuso ideas para hacer de la lectura de textos literarios una experiencia interesante para los estudiantes de EFL. El enfoque del estudio es la evaluación de las actitudes y percepciones de los estudiantes y docentes de segundo año de EFL en la Facultad de Idiomas y Traducción, Universidad Islámica Imam Muhammad Ibn Saud (IMBSIU) y Facultad de Ciencias y Artes, Methnab, Universidad de Qassim (QU), hacia estudiar literatura en inglés. El estudio intentó conciliar y unir las preferencias literarias de los alumnos con los objetivos educativos con respecto a los componentes literarios en las aulas sauditas de inglés como lengua extranjera. Los hallazgos fueron múltiples, pero en general mostraron mejores resultados después de la administración del tratamiento, especialmente en términos de motivación, compromiso y producción comunicativa.